TLR7 Protein Expression in Mild and Severe Lupus-Prone Models Is Regulated in a Leukocyte, Genetic, and IRAK4 Dependent Manner - Celhar, Teja; Lu, Hao Kim; Benso, Lia; Rakhilina, Larissa; Lee, Hui Yin; Tripathi, Shubhita; Zharkova, Olga; Ong, Wei Yee; Yasuga, Hiroko; Au, Bijin; Marlier, Damien; Lim, Lina Hsiu Kim; et al. (Frontiers in Immunology, 2019)
The global increase in autoimmunity, together with the emerging autoimmune-related side effects of cancer immunotherapy, have furthered a need for understanding of immune tolerance and activation. Systemic lupus erythematosus (SLE) is the archetypical autoimmune disease, affecting multiple organs, and tissues. Studying SLE creates knowledge relevant not just for autoimmunity, but the immune system in general. Murine models and patient studies have provided increasing evidence for the innate immune toll like receptor-7 (TLR7) in disease initiation and progression. Here, we demonstrated that the kinase activity of the TLR7-downstream signaling molecule, interleukin-1 receptor associated kinase 4 (IRAK4), is essential for mild and severe autoimmune traits of the Sle1 and Sle1-TLR7 transgenic (Sle1Tg7) murine models, respectively. Elimination of IRAK4 signaling prevented all pathological traits associated with murine lupus, including splenomegaly with leukocyte expansion, detectable circulating antinuclear antibodies and glomerulonephritis, in both Sle1 and Sle1Tg7 mice. The expansion of germinal center B cells and increased effector memory T cell phenotypes that are typical of lupus-prone strains, were also prevented with IRAK4 kinase elimination. Analysis of renal leukocyte infiltrates confirmed our earlier findings of an expanded conventional dendritic cell (cDC) within the kidneys of nephritic mice, and this was prevented with IRAK4 kinase elimination. Analysis of TLR7 at the protein level revealed that the expression in immune cells is dependent on the TLR7-transgene itself and/or autoimmune disease factors in a cell-specific manner. Increased TLR7 protein expression in renal macrophages and cDCs correlated with disease parameters such as blood urea nitrogen (BUN) levels and the frequency of leukocytes infiltrating the kidney. These findings suggest that controlling the level of TLR7 or downstream signaling within myeloid populations may prevent chronic inflammation and severe nephritis.